EFFICACY OF THE NEWCASTLE DISEASE VACCINE ON THE CONTROL OF BOVINE PAPILOMATOSIS - Puri C., Oswaldo (2011)
The efficacy of Newcastle disease virus La Sota strain (NDV-LS) attenuated vaccine for treating bovine papillomatosis was evaluated. A total of 64 crossbreed female dairy cattle with clinically diagnosed skin papillomatosis, reared in farms of Alto Mayo, San Martín, Peru were used in the study. A group of 34 animals were subcutaneously inoculated with 2 ml of NDV-LS attenuated vaccine (109 infective dose50 in egg) on day 0 and day 7, and were clinically evaluated on days 0, 7, 30, 45, and 60 after inoculation. The remainderanimals were kept as controls. Effective treatment was considered when at least 75% of papillomas successfully underwent to regression. Evaluation on day 60 showed the treatment to be effective in three animals (8.8%). No statistical difference was found with the control group. No secondary signs were observed in treated animals during the study. In conclusion, La Sota strain attenuated vaccine against Newcastle disease was not effective in treating and controlling bovine papillomatosis in semi-extensively managed animals from Alto Mayo region.